The trajectory of Russian geostrategy: challenges and threats of regional and global security. Review: Oleg Kondratenko’s. Geostrategic Dimension of Foreign Policy of the Russian Federation. Monograph. Kyiv: PРС “Kyiv University”, 2017. 607 p. - Oleg Mashevskyi (Європейські історичні студії, 2018)
The results of the reviewing the geostrategic aspect of foreign policy activity of the Russian Federation have been presented. The analysis of the level of disclosure given by the author of the methodological principles of Russian geostrategy, its planning and key vectors of implementation, has been provided. The estimated level of presentation of the content of the regional vector of Russian geostrategy comes as follows: its priority is to provide geopolitical influence in the post-Soviet space through its reintegration, as well as through the creation of controlled conflicts. The monograph has separately analyzed the degree of disclosure of the essence of the global dimension of geostrategy of the Russian Federation in the context of the West, Middle East, Asia-Pacific, African, Latin American and Arctic foreign policy directions of Russia. Thus, through a number of such directions, Russia attempts to implement its influence on the international security and the emergence of a new world order.